Daniel Wing and Alan Scott: The Bread Builders. Hearth Loaves and Masonry Ovens - Jaine, Tom (Petits Propos Culinaires, 2024)
Daniel Wing and Alan Scott: The Bread Builders. Hearth Loaves and Masonry Ovens: Chelsea Green Publishing Co., White River Junction, Vermont, 1999: ISBN 1-890132-05-5: 253 pp., many drawings and photographs, p/b, $35, approx. £35.